JAUTI22 : XI Jornadas Iberoamericanas sobre Aplicaciones y Usabilidad de la TV Interactiva - Abásolo Guerrero, María José (2024)
The XI Ibero-American Conference on Applications and Usability of Interactive Digital Television (jAUTI 2022) was jointly organized by CITEC of the University of Córdoba (Spain) and RedAUTI (Thematic Network on Applications and Usability of Interactive Digital Television). This conference took place from November 17 to 18, 2022, in the city of Córdoba (Spain), conducted in an online format. This publication compiles 19 research papers that were presented during the conference, covering various topics such as the design, development, and experiences of applications for interactive digital television and related technologies.